134 Comparison of Extent of Tumor Resection and Endocrine Outcomes for Nonfunctioning Pituitary Adenomas of a Less Experienced Surgeon Using a Fully Endoscopic Transsphenoidal Surgery Technique to a Very Experienced Surgeon Using a Microscopic Transsphenoidal Surgical Technique. (August 2015) - Zaidi, Hasan; Bohl, Michael; Awad, Al-Wala; Chapple, Kristina; Knecht, Laura; Jahnke, Heidi; White, William L.; Little, Andrew S.
Abstract : INTRODUCTION: The comparative efficacy of microscopic and fully endoscopic transsphenoidal surgery for pituitary adenomas has not been well studied despite the adoption of fully endoscopic surgery by many pituitary centers. We compared the extent of tumor resection (EOR) and the endocrine outcomes of 1 very experienced surgeon performing a microscopic-transsphenoidal surgery technique (1800 independent cases) with those of a less experienced surgeon using a fully endoscopic-transsphenoidal surgery technique (100 independent cases) for nonfunctioning pituitary adenomas in a concurrent series of patients. METHODS: Post hoc analysis was conducted of a cohort of adult patients prospectively enrolled in a pituitary adenoma quality-of-life study between 2011 and 2014. RESULTS: Fifty-five patients underwent fully endoscopic transsphenoidal surgery, and 80 patients underwent fully microscopic transsphenoidal surgery. Baseline characteristics of the 2 treatment groups were well matched. EOR was similar between the endoscopic and microscopic groups, respectively, as estimated by gross total resection rate (78.2% vs 81.3%, P = .67), percentage of tumor resected (99.2% vs 98.7%, P = .42), and volume of residual tumor (0.12 cm 3 vs 0.20 cm 3, P = .41). Multivariate modeling suggested that preoperative tumor volume was the most important predictor of EOR ( P = .001). No difference was found in the development of anterior gland dysfunction ( P > .14), but there was a higher incidence of permanent posterior gland dysfunction in the microscopic group ( P = .04). Combined rates of major complications and unplanned readmissions were lower in the endoscopic group ( P = .007), but individual complications were not different. CONCLUSION: A less experienced surgeon using a fully endoscopic technique was able to achieve similar outcomes compared with a very experienced surgeon using a microscopic technique in a cohort of patients with nonfunctioning tumors. These data suggest that certain advantages afforded by the fully endoscopic technique help address the learning curve in pituitary surgery.